Associations of prenatal alcohol exposure and offspring harmful alcohol use: findings from the Raine Study. (1st December 2020) - Duko, Bereket; Pereira, Gavin; Betts, Kim; Tait, Robert J.; Newnham, John; Alati, Rosa
Highlights: Offspring exposed to maternal prenatal alcohol use of four or more standard drinks per week during the first and third trimesters had an increased risk of harmful alcohol use at the age of 17 years. Maternal pre-pregnancy alcohol use has no association with an increased risk of harmful alcohol use in offspring. Early screening and prevention of maternal alcohol use during pregnancy could possibly reduce harmful alcohol use in offspring. Abstract: Background: Epidemiological evidence suggests offspring exposed to prenatal alcohol are at increased risk of alcohol use disorders in adulthood. The evidence on the risk of developing harmful alcohol use in adolescence is less clear. Methods: We used data from the Raine Study, a multi-generational birth cohort study, to examine the association between prenatal alcohol exposure and the risk of harmful alcohol use in offspring at the age of 17 years. Log binomial regression was used to estimate the relative risks (RRs) of harmful alcohol use in offspring exposed to maternal alcohol use in the first (early) and third (late) trimesters of pregnancy. Maternal pre-pregnancy alcohol use was used as a negative control for intrauterine exposure for comparison. Results: Complete data were available for 1200 mother-offspring pairs. After adjustment for potential confounders, we found increased RRs of harmful alcohol use in offspring born to mothers who consumed four or more standard drinks of alcohol per week during the first trimester [RR 1.45(95% CI: 1.08−1.93)], third trimester [RR 1.34 (95% CI: 1.04–1.72)] and during both trimesters of pregnancy [RR 1.86 (95% CI: 1.16−2.96)]. Maternal pre-pregnancy alcohol use was not associated with an increased risk of harmful alcohol use in offspring [RR 1.15 (95% CI: 0.89−1.48)]. Conclusion: Observed associations for maternal prenatal alcohol exposure but not maternal pre-pregnancy alcohol use suggests a biological mechanism for intrauterine alcohol exposure on the risk of harmful alcohol use in the offspring.